E-learning with the Application Google Classroom for German in Class X Students at Madrasah Aliyah Negeri 1 Jembrana Bali - Chusnul Dwi Rahayu; Sawitri Retnantiti (Universitas Negeri Malang, 2022)
The purpose behind this research is to find out e-learning using the application google classroom for German class X Madrasah Aliyah Negeri 1 Jembrana. Researchers used quantitative research methods using statistical techniques and questionnaire data collection with a sample of 26 students. The data of this study were analyzed using SPSS version 23 which is an indicator of the effectiveness of the use of the application google classroom (Variable X) at point number 8 which is 77.33 percent and the indicator of student response in the ease of accessing the application google classroom at points number 1 and 2 is 77.40 percent. As for the indicators of understanding of learning outcomes in items 9 and 11 of 60.80 percent and indicators of application of items 12 and 13 of 66.76 percent. The final result of this study shows the use of e-learning with google classroom for German in class X MAN 1 Jembrana, the value of the T-test is obtained P value (0.000 less than 0.05), then e-learning with google classroom is applied to German class X leads to improvement in grades.Keywords: e-learning with google classroom, learning outcomes, German